Retroperitoneal solitary neurofibroma mimicking lymph node metastasis of colon cancer: a case report - Takahiro Haruna; Hideyuki Takata; Satoshi Mizutani; Akira Katsuno; Ryosuke Nakata; Norio Motoda; Nobuhiko Taniai; Hiroshi Yoshida (Surgical Case Reports, 2023)
Abstract Background A neurofibroma is a benign tumor that arises from Schwann cells and neurofibromas occur throughout the skin of neurofibromatosis type 1 (NF-1: Von Recklinghausen’s disease) patients. A retroperitoneal solitary neurofibroma without any clinical signs of NF1 has been rarely reported. Herein, we present a case of a retroperitoneal solitary neurofibroma mimicking lymph node metastasis of colon cancer as well as a literature review. Case presentation An 80-year-old woman with abdominal pain and nausea was transported and diagnosed with bowel obstruction arising from sigmoid colon cancer A colonic stent was inserted to alleviate the bowel obstruction. A computed tomography scan with contrast revealed a liver tumor in segment 3, and an enlarged lymph node around the abdominal aorta. Whole-body 18F-fluorodeoxyglucose-positron emission tomography–CT (FDG-PET–CT) examine revealed increased FDG uptake in the liver tumor and enlarged lymph node. Liver and distant lymph node metastasis were diagnosed and we made a plan for a two-stage operation of the colon cancer and the metastatic lesions because laparotomy resection was needed for the retroperitoneal lymph node. Laparoscopic sigmoid colectomy was performed first. Pathological examination showed a tubular adenocarcinoma. A laparotomy for the metastatic lesions was performed to ensure complete lymph node dissection secondly. Histopathological findings of the liver tumor showed metastasis of sigmoid colon cancer. However, the tissue regarded as the enlarged lymph node was diagnosed as a neurofibroma. No metastasis and recurrence were observed. Conclusion Although most neurofibromas are benign, malignant transformation of a neurofibroma is possible. PET–CT showed our patient had a high accumulated retroperitoneal tumor co-existing with colon cancer and liver metastasis. The treatment strategy of a solitary neurofibroma must be selected carefully considering the site of occurrence and the patient’s background and aggressive resection of a tumor co-existing with another malignant tumor is needed.